Vulnerability analysis of pile-reinforced slope under the condition of near-fault impulse ground motions. Issue 6 (October 2021) - Tao, L J; Jia, Z B; Bian, J; Shi, M; An, S; Zhang, Y
Abstract: In order to analyze the impact of the near-fault pulse ground motions on the slope, the method of seismic vulnerability analysis based on IDA is introduced into the stability evaluation. Taking the slope reinforced by stabilizing piles as an example, a typical analysis model is established. The seismic performance is divided into four stages: basically intact, partial damage, severe damage and overall instability. A large number of calculations are used to compare the instability probability of slopes with near-fault and far-field ground motions. The results show that: 1) The calculation model which combines the Newmark and the limit analysis method can reflect the difference between the near-fault and the far-field ground motions. 2) The IM-DM curve with indexs of PGA and displacement has a better fitting effect. The vulnerability analysis based on IDA can be used to evaluate the slope failure risk under seismic loads. 3) The IDA curve shows a monotonous increasing trend. When the seismic intensity is lower(GPA=0∼0.5), there is no obvious difference between the vulnerability curves of the near-fault and far-field. As the intensity increases(GPA=0.5∼1.2), the failure probability of near-fault is significantly higher than the far-field. Meanwhile, the failure mode changed from the partial failure to the complete failure. It is clear that near-fault ground motions have the characteristics of large energy and strong impact, which are more likely to cause slope instability. If the impact of the near-field earthquake is ignored, the disaster may be underestimated.